Botulinum toxin applications at doses appropriate for aesthetic procedures: Effect on tension type headache (Annals of Medical Research, 2021)
Aim: Prophylactic treatment options for tension-type headache are limited. Studies have demonstrated beneficial effects of botulinum toxin-A in headache suffers. This study aimed to evaluate the effect of application of Btx-A at normal aesthetic procedure doseage in the treatment of tension-type headache.Material and Methods: Forty-six patients (37 females; 80.4%), were included in the study, sub-divided by type of head-ache; chronic or episodic. All patients received 55 UI botulinum toxin-A. Pain frequency and severi-ty were evaluated by neurological examination and visual analog scale, before application, three and six months after application. Results were compared at time points and between the groups.Results: Mean±standard deviation age of the patients was 41.80±8.36 years. Episodic and chronic tension-type headache was present in 54.3% (n = 25) and 45.7% (n = 21), respectively. In both episodic and chronic tension-type headache there was a significant reduction in visual analog score score at both the third (p=0.001) and sixth (p=0.001) months post-application compared with preapplication. However, visual analog score scores significantly worsened by the sixth month compared to the third month (p=0.01 and p=0.007 for episodic and chronic tension-type headache, respectively) while remaining improved compared to baseline. In episodic tension-type headache, frequency of occurrence decreased significantly at the third (p=0.025) but not at the sixth (p=0.16) months com-pared to baseline. In chronic tension-type headache there was no difference in the frequency of ten-sion-type headache at any time point (p>0.05).Conclusion: We believe that there may be a role for low dose botulinum toxin-A in the prophylactic treatment of tension-type headache but further larger studies are required to confirm this and identify the optimal dose.
Keywords: Botulinum toxin; headache; tension-type; treatment